Legal kidnapping. Special attention to the implementation of Convention 25 October 1980 and the exception for the immediate return of the child - Lorente Martínez, Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
Cases of international child abduction imply great challenges for the legal operators who must respond to them. The recent judgment of the Provincial High Court of León 12 May 2020 provides answers as to what should be considered a wrongful transfer retention of a child, what is the real object of The Hague Convention 25 October 1980, the questions of the burden of proof in these proceedings, and the circumstances experienced by the mother and the consequences for the retention of a child from British Columbia (Canada) to Spain. All of them are the subject to analysis in this paper.
Keywords: legal kidnapping; international; child; exception; civil aspects